2022
DOI: 10.1016/j.jbc.2021.101555
|View full text |Cite
|
Sign up to set email alerts
|

Selective activation of TRPA1 ion channels by nitrobenzene skin sensitizers DNFB and DNCB

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Although the amino acid numbers differ, the binding pocket around the S4-S5 linker in TRPV1 of SC competing with AITC or CAP simulated in this study is quite similar to the previously published simulation of CAP binding to TRPV1, referring to the TRPV1 structure identified (42, 43). While the major simulations of AITC and SC demonstrated lower binding energy to the intracellular AR16 or the Linker domain in the N-terminus, the disturbance of SC in the Pre-S1 helix and the TRP-like domain seems more convincing, compared to the simulation of DNCB and DNFB, agonists of TRPA1 to trigger itch as AITC, binding to TRPA1 in protein pockets around the Linker domain and the TRP-like domain (44). Further studies focusing on protein pockets identified to testify whether SC is a competitive inhibitor of TRPV1 and TRPA1 are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Although the amino acid numbers differ, the binding pocket around the S4-S5 linker in TRPV1 of SC competing with AITC or CAP simulated in this study is quite similar to the previously published simulation of CAP binding to TRPV1, referring to the TRPV1 structure identified (42, 43). While the major simulations of AITC and SC demonstrated lower binding energy to the intracellular AR16 or the Linker domain in the N-terminus, the disturbance of SC in the Pre-S1 helix and the TRP-like domain seems more convincing, compared to the simulation of DNCB and DNFB, agonists of TRPA1 to trigger itch as AITC, binding to TRPA1 in protein pockets around the Linker domain and the TRP-like domain (44). Further studies focusing on protein pockets identified to testify whether SC is a competitive inhibitor of TRPV1 and TRPA1 are needed.…”
Section: Discussionmentioning
confidence: 99%